Performa Ayam Broiler yang Diberi Ekstrak Daun Jambu Mete (Anacardium occidentale Linn) dalam Air Minum: Performance of Broiler Chicken with Inclusion Cashew Leaf Extract (Annacardium occidentale Linn) in Water Drinking - S Khothijah; Edi Erwan; E Irawati (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2021)
Cashew leaves (Anacardium occidentale Linn) is a plant that can be used as a natural antibiotic because it contains flavonoids, tannins, anacardiol acid, elagic acid, phenol compounds, cardol, and methyl cardol. The aim of this study was to determine the effect of giving several levels of consumption of cashew leaf extract in drinking water on the performance of broilers including ration consumption, drinking water consumption, body weight gain, and ration conversion. This study used 80 doc broilers which were divided randomly based on a completely randomized design with 5 treatments and 4 replications. The treatments given were P0 (0% cashew leaf extract as a control), P1 (5% cashew leaf extract in 1 L of water), P2 (10% cashew leaf extract in 1 L of water), P3 (15% cashew leaf extract in 1 L of water) and P4 (20% cashew leaf extract in 1 L of water). The variables observed were ration consumption, drinking water consumption, body weight gain and broiler ratio conversion. The results showed that inclusion of cashew leaf extract up to 20% in drinking water had a significant effect (p<0.05) on drinking water consumption, but no significant effect on ration consumption, body weight gain, and ration conversion. It was concluded that giving cashew leaf extract in drinking water up to 20% had no effect on the broiler performance, in terms of ration consumption, body weight gain and ration conversion. Key words: broiler chicken, cashew leaf extract, ration consumption, drinking water consumption, body weight gain, ratio conversion